2010
DOI: 10.1039/c0jm02416c
|View full text |Cite
|
Sign up to set email alerts
|

Post-synthetic modification of the metal–organic framework compound UiO-66

Abstract: Post-synthetic modification is a viable route for the introduction of surface sites with new chemical properties in metal-organic framework compounds. Herein we demonstrate that it is possible to perform covalent post-synthetic modifications of the UiO-66-NH 2 MOF with four different acid anhydrides. FT-IR is employed to monitor the reactions and the extent of reaction depends on the bulkiness of the anhydrides. For the smallest one, acetic anhydride, 100% conversion to UiO-66-NHCOCH 3 was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
252
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(268 citation statements)
references
References 16 publications
15
252
0
1
Order By: Relevance
“…The PXRD pattern of UiO-66-NH 2 was in agreement with the reported UiO-66-NH 2 (Fig. 4a) [39], which indicated that the desired material was obtained. The X-ray diffraction peaks of UiO-66-Sal and the UiO-66-Sal-CuCl 2 are the same as the UiO-66-NH 2 (Fig.…”
Section: Characterization Of Zr-mof Catalystsupporting
confidence: 84%
“…The PXRD pattern of UiO-66-NH 2 was in agreement with the reported UiO-66-NH 2 (Fig. 4a) [39], which indicated that the desired material was obtained. The X-ray diffraction peaks of UiO-66-Sal and the UiO-66-Sal-CuCl 2 are the same as the UiO-66-NH 2 (Fig.…”
Section: Characterization Of Zr-mof Catalystsupporting
confidence: 84%
“…S2 and S3 of supporting information). Diffuse reflectance spectra display maxima around 450 nm consistent with a Ru(dπ 6 )→ Ru(dπ 5 )bpy(π*) metalto-ligand charge transfer transition of singlet character, 1 MLCT, common to ruthenium(II) tris(2,2'-bipyridine) and its derivatives. 37 The emission spectra display a maxima at ~ 610 nm.…”
Section: Resultsmentioning
confidence: 97%
“…The physical properties of these three dimensional frameworks can be, and have been, further modified by post-synthetic methods. [1][2][3] Recently, a great deal of interest has been spent on incorporating photoactive ligands as guest molecules in MOFs for potential photovoltaic and photocatalytic applications. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] For example, a series of Re(II), Ir(III), and Ru(II) metal 5,5′-dicarboxy-2,2′-bipyridine, DCBPY, coordination complexes have been incorporated into the Zr(IV) 4,4'-biphenyldicarboxylic acid, BPDC, MOF UiO-67 for the purpose of carbon dioxide reduction, water oxidation, and organic conversion reactions.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive range of PSMs have been already tested on the UiO-66 [19], in particular, the scope to introduce an acidic group raised a significant interest, due to the possibility to produce a highly desired solid Brønsted acid [20][21][22]. In several reported examples a -SO 3 H group was tethered onto the MOF following different synthetic strategies, the prepared materials have been tested as catalysts providing decent results in terms of performances and recyclability.…”
Section: Introductionmentioning
confidence: 98%